Effectiveness Of Butterfly Hug Therapy On Reduction Of Stress And Anxiety Of Students' Anatomy Laboratory Examination Basic Biomedical Sciences Diploma 3 Nursing Study Program - Erik Adik Putra Bambang Kurniawan; I Wayan Sudarta (Journal of health research and technology, 2024)
Background: In order to improve the quality of globally competitive education, the anatomy examination system is very helpful for students in recognizing and understanding anatomy and physiology in basic Biomedical Sciences courses, but it also has the impact of creating feelings of anxiety and stress in preparing for the examination. Excessive anxiety and stress will have an impact on students' psychological problems. One type of therapy that can help deal with stress and anxiety is Butterfly. Butterfly Hug (BH) is a psychotherapy technique to calm anger and get rid of a person's feelings of traumaObjective: To determine the effectiveness of Butterfly Hug Therapy in Reducing Stress and Anxiety in Students in Anatomy Laboratory Exams in Basic Biomedical Sciences for Diploma 3 Nursing Study Program.Method: This research uses a quasi-experimental research method.Research Results: Wilcoxon test results show Asymp. Sig (2-tailed) on the stress level is 0.025. Because the P value < α : 0.05, then Hα is accepted and Hο is rejected, whereas for Asymp. Sig (2-tailed) for anxiety at stress levels is 0.127. Because the P value > α : 0.05, then Hα is rejected and Hο is accepted.Conclusion: There is effectiveness of butterfly hug therapy in reducing stress in students in basic biomedical sciences anatomy laboratory exams and there is no effectiveness of butterfly hug therapy in reducing anxiety in students in basic biomedical sciences OSCE exams in Nursing Diploma 3 Study Program.Suggestion: Future researchers are expected to develop this research, hopefully re-examine the effectiveness of Butterfly Hug Therapy in overcoming mental health problems: anxiety.